IGF1: an in vitro skeletal muscle cell model of exercise mimetics to investigate the role of exosomal trafficking in regulating metabolic responses to exercise - Forte, Marina (2019)
Exercise mimetics are pharmacological compounds that trigger pathways similar to those activated as a consequence of exercise training. They are therefore useful in pathological conditions where physical activity is beneficial but unfeasible. Models of exercise mimetics can also be used to study the targets implicated in training or conversely, inactivity. In the study presented insulin-like growth factor-1 (IGF-1) is investigated as an in vitro model of exercise mimetics, plus or minus the addition of Exo1 drug, that should impair the crosstalk between endoplasmic reticulum and the Golgi apparatus to inquire in its role in exercise metabolism